Comparing antioxidant and cytoprotective effects: Quercetin glycoside vs. aglycone from Ephedra alata - Ezzouhra El Maaiden; Najeeb Ullah; Amine Ezzariai; Adil Mazar; Hassan Boukcim; Abdelaziz Hirich; Boubker Nasser; Nagib Qarah; Lamfeddal Kouisni; Youssef El Kharrassi (Elsevier, 2024)
Background: A wide range of chronic diseases is associated with ROS-mediated oxidative stress. Quercetin glycoside (QG) is reported to be a powerful antioxidant with extremely high bioavailability and structural stability compared to quercetin aglycone. Hypothesis/Purpose: In this study, the antioxidant potential and cytoprotective effects of quercetin, and its glycosides isolated from Ephedra alata against oxidative damage induced by hydrogen peroxide in the cells of tetrahymena pyriformis (TEP) were evaluated and compared. Study design: Quercetin and its O-glycosides were isolated from Ephedra alata, and their chemical structures were elucidated using advanced spectroscopic techniques. The antioxidant and cytoprotective effects were evaluated using TEP cells exposed to hydrogen peroxide-induced oxidative stress. Methods: TEP cells were pretreated with quercetin aglycone (Q), isoquercetin (ISQ), or hyperin (HYP) before exposure to hydrogen peroxide (H2O2). Cell viability, lactate dehydrogenase (LDH) release, intracellular ROS levels, malondialdehyde (MDA levels, lipoperoxidation, antioxidant enzyme activity, and cleaved caspase-3 levels were measured. Results: ISQ pretreatment significantly enhanced cell survival and reduced H2O2-induced LDH release compared to Q. ISQ also decreased intracellular ROS levels, MDA levels, and lipoperoxidation, surpassing the effects of Q. Additionally, ISQ and HYP pretreatment notably increased antioxidant enzyme activity, outperforming Q. Furthermore, ISQ pretreatment significantly diminished cleaved caspase-3 levels compared to Q, indicating a potential role in preventing oxidative stress-induced apoptosis in TEP cells. Conclusion: Quercetin O-glycosides, particularly isoquercetin, from Ephedra alata exhibit superior antioxidant and cytoprotective effects compared to quercetin aglycone. These findings highlight the potential of these compounds as natural alternatives for mitigating oxidative damage and promoting cellular health. Future research should focus on elucidating the precise molecular pathways involved and evaluating their efficacy in animal models and clinical settings.